Analysis of Nonverbal Communication in the Cartoon Series Shaun the Sheep Episode We Wish a Merry Christmas - Hidayatul Aini; Abdul Aziz Wahab; Ivonne Hafidlatil Kiromi (Cendikia : Media Jurnal Ilmiah Pendidikan, 2023)
Nonverbal communication is communication that is done only by using gestures, facial expressions and eye contact. The function of nonverbal communication for early childhood is to stimulate children's motor and sensory abilities, it can also increase children's imagination. There are several cartoons that use nonverbal communication, one of which is the Shaun The Sheep cartoon. In the Shaun The Sheep program, the researcher chose an episode of We Wish A Merry Christmas which tells a story where livestock owners feel sad because they don't have Christmas accessories, Bitzer and Shaun know that they and other sheep are working together to make Christmas accessories for livestock owners. This cartoon uses nonverbal communication in which it can increase the audience's imagination as well as teach children mutual cooperation, mutual assistance and tolerance. Researchers also use nonverbal theory to involve creating and interpreting messages using only body movements and facial expressions